(untitled) (Islamic Sciences Journal, 2026)
The first major crisis that befell the Muslims after the Prophet’s (peace and blessings be upon him) passing, the repercussions of which we still grapple with, was the first military conflict, the shock of which we still feel, stemming from the disagreement among the Prophet’s (peace and blessings be upon him) companions regarding the successor. To honor the most prominent schools of thought that emerged after the Prophet’s (peace and blessings be upon him) passing: Sunni, Shia, and Kharijite. Among these schools of thought is the Sunni school, which holds that the consensus of the Muslim community is the source of legitimacy, based on the principle of consultation and free choice. This aligns with the spirit of the age in selecting the caliph through consultation and presenting the choice to the people of authority (parliament) for ratification. This research addresses this issue and seeks to shed light on the view of Ahlus Sunnah wal Jama’ah (the Sunni community) regarding the caliphate and its implications. Its scholarly content is divided into several sections, culminating in a conclusion that presents the findings and recommendations.